PENERAPAN ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI BERMAIN LILIN (PLASTISIN) TERHADAP KECEMASAN ANAK USIA PRASEKOLAH AKIBAT HOSPITALISASI DI RSPAD GATOT SOEBROTO - Zahra Amanda Nurhaliza (2023)
Anxiety is a feeling that arises when you are worried or afraid of something. This also occurs in pre-school children (aged 3-5 years), where they tend to experience anxiety due to hospitalization. As when the nurse will perform medical actions on children, they tend to cry immediately, and are reluctant to have medical or nursing actions performed. This also happens to preschool children who are undergoing hospitalization at Gatot Soebroto Army Hospital. The purpose of this study was to analyze the application of nursing care interventions, namely children who are hospitalized due to anxiety can benefit from candle play therapy. at Gatot Soebroto Army Hospital. The application of wax play therapy (plasticine) is carried out to managed patients and resume patients which are carried out as many as 3x meetings for 20-30 minutes. Anxiety score data using Scas Preschool. The results of the application of wax play therapy (plasticine) obtained a decrease in preschool children's anxiety due to hospitalization, namely in managed patients the original anxiety score was 54 then decreased to 23, while for resume patients the original anxiety score was 44 then decreased to 10. Keywords: Hospitalization, Anxiety, Preschooler, Candle Play Therapy